The effect of generalized absence seizures on the progression of kindling in the rat - ONAT, FİLİZ; GÜLHAN, REZZAN (BLACKWELL PUBLISHING, 2007)
The involvement of the thalamus in limbic epileptogenesis has recently drawn attention to the connectivity between the nuclei of the thalamus and limbic structures. Thalamo-limbic circuits are thought to regulate limbic seizure activity whereas thalamocortical circuits are involved in the expression and generation of spike-and-wave discharges (SWDs) in the absence epilepsy models. Genetic Absence Epilepsy Rats From Strasbourg (GAERS) and WAG/Rij (Wistar Albino Glaxo from Rijswijk) are well-defined genetic animal models of absence epilepsy. We aimed to examine the duration of behavioral changes in the kindling process and the relation of SWD activity to the kindling progress in the GAERS and WAG/Rij animals. Electrodes were stereotaxically implanted into the basolateral amygdala and the cortex of rats for stimulation and recording. The animals were stimulated at the threshold for producing afterdischarges. EEG was recorded to analyze SWDs and afterdischarge durations. The seizure severity was evaluated using Racine's 5-stage scale. None of the GAERS animals reached stage 3, 4, or 5 after application of 30 stimulations. The WAG/Rij animals showed different rate of kindling, therefore they were further categorized into the kindling-resistant, slow-kindled, and rapid-kindled groups. The kindling-resistant animals demonstrated a significantly longer duration of SWDs on the first day of the experiment before kindling stimulation and shorter duration of afterdischarge than did the kindled WAG/Rij animals. Behavioral durations at stage 2 were longer in kindled Wistar and WAG/Rij animals compared to kindling-resistant WAG/Rij and GAERS. These results suggest that mechanisms involved in the generation of SWDs act as a counterbalance to the excitability induced by kindling.
Keywords: temporal lobe epilepsy model; absence epilepsy models; GAERS; WAG/Rij; generalized epilepsy; kindled; THALAMIC RETICULAR NUCLEUS; ELECTRICAL-STIMULATION; EPILEPSY; MECHANISMS; COMPLEX; MODELS; CORTEX; CA1